How Globalization Really Happens: Remembering Activism in the Transformation of Istanbul. (12th December 2014) - Houston, Christopher
Abstract Over the past 20 years it has become accepted wisdom that Istanbul has become a 'global city', transformed in tandem with a raft of neoliberal economic policies. What is the relevant history of this globalization? A muted local knowledge possessed by Istanbul's inhabitants is that the military coup in 1980 was the crucial event in the re‐engineering of the city. Yet exactly here a contradiction emerges: despite this acknowledgement, there is apparently little public memory about what it was like to study, work and agitate in Istanbul in the 'crisis' years before the coup. Based on extensive interviews with people active in political fractions in the late 1970s, this article privileges a phenomenological approach to identify spatial practices, performances and perceptions of activists that generated and structured Istanbul's expanding urban environment in that period. Further, it shows how this history is relevant for comprehending both the 'micro‐causes' of the coup as well as important dimensions of Turkish politics in the present, each of which cast illuminating light on Istanbul's experience of globalization.